Ecological studies on keratinophilic fungi - Ibbotson, R. (1974)
The seasonal distribution of keratinophilic fungi bas been studied in the soils surrounding an outdoor swimming pool and in soils of summer pens of hedgehogs. The species isolated were conidial and cleistocarpic Arthroderma uncinatum, Trichohyton terrestre, Chrysosorium keratinophilum, Microsporum cookei and Microsporum gypseum. A correlation between some species and. The numbers of hedgehogs in the pens was seen, due to the influence of keratin provided by the quills and scales of the hedgehogs. No such relationship was seen at the swimming pool, although conidial A. uncinatum was seen to decrease when the swimming pool was open to the public in the summer. However, this appears to be the normal seasonal occurrence since a similar pattern of distribution in soils collected from outside the swimming pool was seen.